A Nationwide, Multicenter Registry Study of Antiemesis for Carboplatin‐Based Chemotherapy‐Induced Nausea and Vomiting in Japan. (21st October 2019) - Iihara, Hirotoshi; Shimokawa, Mototsugu; Hayashi, Toshinobu; Kawazoe, Hitoshi; Saeki, Toshiaki; Aiba, Keisuke; Tamura, Kazuo
Abstract: Background: We previously reported the results of a prospective study of chemotherapy‐induced nausea and vomiting (CINV) in a cohort of patients who received carboplatin‐based chemotherapy and were selected from a nationwide registry of those scheduled for moderately (MEC) or highly emetogenic chemotherapy (HEC) by the CINV Study Group of Japan. Of 1, 910 previously registered patients (HEC: 1, 195; MEC: 715), 400 patients received carboplatin‐based chemotherapy. The frequency of CINV was determined, and the risk factors for CINV were assessed. Materials and Methods: CINV data were collected from 7‐day diaries. Risk factors for CINV were identified using logistic regression models. Results: Of 400 patients scheduled for carboplatin‐based chemotherapy, 267 patients received two antiemetics (5‐hydroxytryptamine‐3 receptor antagonist [5‐HT3 RA] and dexamethasone [DEX]), 118 patients received three antiemetics (5‐HT3 RA, DEX, and neurokinin‐1 receptor antagonist [NK1 RA]), and 15 were nonadherent to the treatment. In these patients, the CINV overall, acute, and delayed phase rates of complete response (CR), defined as no vomiting with no rescue medication, were 67.0%, 98.2%, and 67.5%, respectively. The rates of no nausea were 55.6%, 94.0%, and 56.1%, respectively, and those of no vomiting were 81.3%, 99.0%, and 81.8%, respectively. Older age was associated with a decreased non‐CR, whereas female sex, history of pregnancy‐related emesis, and dual antiemetic therapy were associated with an increased non‐CR during the overall period. Conclusion: In a clinical practice setting, in patients who received carboplatin‐based chemotherapy, adherence is quite high and appropriate antiemetic prophylaxis requires a triple antiemetic regimen including NK1 RA. Implications for Practice: For patients receiving carboplatin‐based chemotherapy, triple antiemetic therapy with 5‐hydroxytryptamine‐3 receptor antagonist, dexamethasone, and neurokinin‐1 receptor antagonist should be given prophylactically regardless of risk factor status. Abstract : Chemotherapy‐induced nausea and vomiting reduces quality of life and treatment adherence. This article reports on the incidence of this adverse event and identifies risk factors using a nationwide registry of patients who underwent carboplatin‐based chemotherapy.